microRNA-145-5p inhibits prostate cancer bone metastatic by modulating the epithelial-mesenchymal transition - Luo, Bingfeng; Yuan, Yuan; Zhu, Yifei; Liang, Songwu; Dong, Runan; Hou, Jian; Li, Ping; Xing, Yaping; Lu, Zhenquan; Lo, Richard; Kuang, Guan-Ming (Frontiers in Oncology, 2022)
Objective: To investigate effects of miRNA-145-5p, a member of the group of microRNAs, small noncoding RNAs which influence tumor development and progression, on prostate cancer (Pca) bone metastasis.Methods: Levels of miRNA-145-5p were assessed by real-time quantitative PCR in the PC3 (bone metastatic Pca cells), 22RV1 (non-metastatic Pca cells), RWPE-1 (non-cancerous prostate epithelial cells), and Pca tissues collected from patients with and without bone metastases. The impact of miRNA-145-5p on cell proliferation was tested by CCK8 assay, colony formation assay and flow cytometric cell cycle analysis. Effects on invasion and migration of PC3 cells were determined by Transwell and wound healing assays. Western blotting, enzyme linked immunosorbent assay, and flow cytometry apoptosis analyses were also performed to assess roles in metastasis.Results: Levels of miRNA-145-5p were decreased in Pca bone metastases and miRNA-145-5p inhibited cell proliferation, migration and invasion. It was found that miRNA-145-5p mediated the epithelial-mesenchymal transition (EMT) and induced apoptosis.Conclusions: miRNA-145-5p regulated the EMT and inhibited Pca bone metastasis and promoted apoptosis in Pca bone metastasis cells. Mimicry of miRNA-145-5p action raises the possibility of a novel target for treating Pca with bone metastases.